Inhibition of ghrelin o-acyltransferase attenuated lipotoxicity by inducing autophagy via AMPK–mTOR pathway - Zhang S; Mao Y; Fan X (Dove Medical Press, 2018)
Shaoren Zhang, Yuqing Mao, Xiaoming Fan Department of Gastroenterology and Hepatology, Jinshan Hospital of Fudan University, Shanghai, China Background: Nonalcoholic fatty liver disease (NAFLD) has been considered the most commonly occurring chronic hepatopathy in the world. Ghrelin o-acyltransferase (GOAT) is an acylation enzyme which has an acylated position 3 serine on ghrelin. Recent investigation revealed that activated autophagy could attenuate liver steatosis. The aim of this study was to explore therapeutic roles that inhibit GOAT exerted in NAFLD, and its potential association with autophagy.Materials and methods: Human LO2 cells were pretreated with siRNA-GOAT to induce liver steatosis using free fatty acids (FFAs). A chronic NAFLD model was established by feeding male mice C57bl/6 with high-fat diet (HFD) for 56 days with GO-CoA-Tat administrated subcutaneously. Lipid droplets were identified by Oil Red O stains. Body weight (BW) of mice was measured every week. Autophagy, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), serum biochemical indicators (glucose [Glu], total cholesterol [TC], triglyceride [TG], aspartate aminotransferase [AST], alanine aminotransferase [ALT]) and signaling pathway proteins of phosphorylated AMPK–mTOR were measured.Results: The TG contents of the FFA and HFD groups were decreased by the inhibition of GOAT. Among mice treated with GO-CoA-Tat and siRNA-GOAT, IL-6 and TNF-α concentrations were remarkably decreased. Indicators of liver injury such as ALT and AST were also remarkably decreased among mice treated with GO-CoA-Tat. Likewise, GO-CoA-Tat significantly reduced the BW of mice and serum TG, TC and Glu. Autophagy was induced along with reduced lipids in the cells of the FFA and HFD groups. The inhibition of GOAT upregulated autophagy via AMPK–mTOR restoration.Conclusion: These results indicate that the inhibition of GOAT attenuates lipotoxicity by autophagy stimulation via AMPK–mTOR restoration and offers innovative evidence for using GO-CoA-Tat or siRNA-GOAT in NAFLD clinically. Keywords: ghrelin o-acyltransferase, GOAT, high-fat diet, HFD, free fatty acid, FFA, nonalcoholic fatty liver disease, NAFLD